Shinjuku Boys - Longinotto, Kim; Williams, Jano (Bookbinder, Alan, 1995)
Duration: 00:55:00 The boys in the title are actually onnabes, or cross-dressing Japanese girls, who work as hosts at the New Marilyn club in Tokyo. They are women who live as men and have girlfriends, although they don't usually identify as lesbians. As the film follows them at home and on the job, all three talk frankly to the camera about their gender-bending lives, revealing their views about women, sex, transvestitism and lesbianism. Alternating with these illuminating interviews are fabulous sequences shot inside the club, patronized almost exclusively by heterosexual women who have become disappointed with real men. This is a remarkable documentary about the complexity of female sexuality.